2016
DOI: 10.3823/1959
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ knowledge and practices regarding chronic kidney disease at a tertiary care hospital

Abstract: Background: The complications of chronic kidney disease (CKD) significantly contribute to morbidity and mortality, therefore clinical practice guidelines have been developed to facilitate early detection and treatment. However, given the high prevalence of CKD, many patients with early CKD are seen by non-nephrologists, who need to be aware of CKD complications, screening methods and treatments goals in order to initiate timely therapy and referral.Methods: This was a cross-sectional study conducted at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Our study participants often prescribe drugs such as βBlockers, Thiazide Diuretics, and Angiotensin Converting Enzyme (ACE) inhibitors to patients with CKD. Rubeen et al 2009 and many others [37][38][39][40][41][42][43][44][45] have reported the same nding. Dialysis and kidney transplant are the other treatment options for patients with ESKD.…”
Section: Discussionsupporting
confidence: 54%
“…Our study participants often prescribe drugs such as βBlockers, Thiazide Diuretics, and Angiotensin Converting Enzyme (ACE) inhibitors to patients with CKD. Rubeen et al 2009 and many others [37][38][39][40][41][42][43][44][45] have reported the same nding. Dialysis and kidney transplant are the other treatment options for patients with ESKD.…”
Section: Discussionsupporting
confidence: 54%
“…Our study participants often prescribe drugs such as βBlockers, Thiazide Diuretics, and Angiotensin Converting Enzyme (ACE) inhibitors to patients with CKD. Rubeen et al 2009 and many others [ 32 , 36 43 ] have reported the same finding. Dialysis and kidney transplant are the other treatment options for patients with ESKD.…”
Section: Discussionsupporting
confidence: 54%
“…In Ethiopia because of the poor infrastructure, poor laboratory facility and shortage of manpower in the area, physicians frequently use urine and serum creatinine as a means of CKD diagnosis. However, serum creatinine and urine diagnosis may not truly indicate the different stage of CKD, because creatinine level might increases in the blood after high protein ingestions, intense exercise and after taking some drugs such as Cimetidine, Trimethoprim, Pyrimethamine, Salicylates, Phenacemide, Corticosteroids, and Vitamin D derivatives [35,36]. Increasing evidence indicates that the CKD burden is increasing in developing countries.…”
Section: Discussionmentioning
confidence: 99%